DETEKSI DINI TUMBUH KEMBANG ANAK USIA DINI DI TPA SERAMA: - Wiyarni Pambudi (Jurnal Bakti Masyarakat Indonesia, 2026)
The Serama Childcare Center faces challenges in monitoring child growth and development after the COVID-19 pandemic, including nutritional variations, developmental delays, and suboptimal feeding practices. This community service activity aimed to integrate Early Detection and Intervention for Growth and Development (SDIDTK) into TPA Serama services as a solution to strengthen institutional childcare quality. A total of 24 children aged 5 to 56 months were assessed using standardized instruments: WHO growth charts, KPSP, KMME, vision and hearing screening, perinatal and medical history, personal hygiene, and PMBA practices. Results showed that most children had normal nutritional status and age-appropriate development, though some cases of stunting, underweight, and mild behavioral issues were detected. Feeding practices were not yet optimal, with screen time during meals and forced feeding still observed. This activity demonstrates that integrating SDIDTK and nutrition education into institutional childcare is feasible and beneficial for supporting holistic child growth and development.